In vitro regeneration of kunyit hitam (curcuma caesia roxb.) - Fong, Yin Mei (Universiti Malaysia Sarawak (UNIMAS), 2012)
Curcuma caesia Roxb. is one of the species under genus Curcuma. It is called ‘Kunyit Hitam’ (Malay), Black Zedoaia (English), Nilkantha (Bengal) and Manupasupu (Telugu). It is a non-native plant in Malaysia. The present study was to establish an efficient surface sterilization technique and protocol for C. caesia. Leaves and rhizome buds of C. caesia were used as explants. The leaf explants part was lamina and midrib. They were surface sterilized using 70% ethanol and Clorox®. Axenic lamina and midrib were transferred into full solid MS medium supplemented with 1.0, 2.0, 3.0, or 4.0 mg/L of 2, 4-Dichlorophenoxyacetic acid (2, 4-D) in combination with 0.5 mg/L of 6-benzylaminopurine (BAP) for callus induction. The highest number of explants induced calli was in medium 1.0 mg/L of BAP with 0.5 mg/L of BAP. However, some of explants that produced calli started to become yellowish brown, dry and then died. Some of them were still alive but went slow growth of callus. As for rhizome buds, they were surface sterilized by using 70% (v/v) of ethanol for 1 minute, followed by 40% (v/v) of Clorox® (20 minutes) added with a few drops of Tween-20 and rinsed with sterile distilled water. Then, the explants were inoculated in ½ MS (Murashige and Skoog) basal medium for two weeks. The percentage of axenic explants obtained after surface sterilization was 28 %. After that, the axenic explants were cultured in ½ MS supplemented with 1.0, 3.0 and 5.0 mg/ml of BAP either alone or with 0.5 mg/L of indole-3-butyric acid (IBA) for multiple shoot induction. The explants produced multiple shoots after 2 to 3 weeks of culture. Rooting and callus formation also had been recorded. Higher percentage of axenic explants also had been recorded when media was supplemented with 4 mg/L of plant preservative mixture (PPM) and 4 mg/L of tetracycline. The highest multiple shoot proliferations were recorded in medium supplemented with 1.0 mg/L BAP.